2019
DOI: 10.1016/j.jval.2019.04.1911
|View full text |Cite
|
Sign up to set email alerts
|

Are Global Health Systems Ready for Transformative Therapies?

Abstract: Background: We have seen significant advancement in a range of health technologies, some with transformative or curative potential. Nevertheless, it is often unclear how global health systems recognize or reward innovation. Objectives:To consider what is transformative, challenges for transformative therapies, and downstream health ecosystem effects.Methods: A systematic review of publications in English between 2012 and 2018 was conducted with a focus on value assessment processes and health system effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Indeed, acceleration in this field is anticipated with ongoing innovation, including for example the introduction of additive manufacturing technology, digital design and use of artificial intelligence for biofabrication of functional organ structure [27]. As regenerative therapies continue to permeate the future clinical landscape with validated solutions and confirmed utility, global readiness for clinical adoption must be prioritized [28,29]. Yet the portal for next-generation healthcare providers to access adequate training in regenerative care counseling remains narrow.…”
Section: Future Perspectivementioning
confidence: 99%
“…Indeed, acceleration in this field is anticipated with ongoing innovation, including for example the introduction of additive manufacturing technology, digital design and use of artificial intelligence for biofabrication of functional organ structure [27]. As regenerative therapies continue to permeate the future clinical landscape with validated solutions and confirmed utility, global readiness for clinical adoption must be prioritized [28,29]. Yet the portal for next-generation healthcare providers to access adequate training in regenerative care counseling remains narrow.…”
Section: Future Perspectivementioning
confidence: 99%
“…The great burden of this disease with highest risk of suicide among psychiatric disorders, common psychiatric and somatic comorbidities, treatment resistance and devastating psychosocial consequences calls for more effective treatments 53. Clozapine with its unique pharmacology and epigenetic and neuroplastic effects can become a transformative treatment similarly to antiviral transformative treatments for AIDS or HCV, cell therapies in oncology or gene therapies54 or ketamine in the treatment of depression. It can significantly reduce the great burden of BP I and may modify the course of the disease.…”
Section: Concept Of Transformative Treatmentmentioning
confidence: 99%
“…The lack of appetite for complex agreements among policy-makers was also noted by Karlsberg Schaffer et al [5], who concluded that 'there is a mismatch between the enthusiasm in the academic literature for developing new approaches and the scepticism of payers that they can work, or are necessary for the foreseeable future'. Secondly, there has been a growth in the application of financed-based and performance-based agreements to drugs rather than to other types of technologies, which could be a response to the growing number of transformational, but highly expensive new drugs entering the market [6]. Many recent reviews of PBRSAs discuss issues that apply to health technologies in general but draw almost exclusively on drugs for their examples [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%